Hypnoteachingg: Solusi Siswa Learning Disorder - Muhammad Mushfi El Iq Bali; Itatul Masulah (AT-TURATS, 2019)
This study wants to analyze the extent to which the role of hypnoteaching is offered by the world to academics in the education fild to overcome the problem of learning disorder students. The reseach methode used is the reseach library. Based on the reseach it was concluded that hypnoteaching is the most accurate and relevant solution to create the effectiveness of learning disorder learning students, although sometimes only through simple strategies. By hypnoteaching, learning disorder students will feel more likely to be present and not cornered even though their essence is not the same as other normal humans. The implication og this study is that the theories that are conceptualized in hypnoteaching succeed in reducing students’ learning disorder anxiety while participating in learning activities.